Numerical study on heat transfer of turbulent flow in a channel with composite arrangement obstacles - Parsazadeh, M. (2013)
Forced convective heat transfer of turbulent flow in a two-dimensional channel mounted triangular and trapezoidal obstacles in upper wall and bottom wall arranged with periodic grooves is numerically studied. Continuity, momentum and energy equations are discretized with second order upwind method is applied to solve the equations. (RNG) k-ε model is implemented to predict the thermo-hydraulic performance of the flow. A thick of 3mm made up by aluminum is implemented for channel walls that the bottom and upper walls are heated with a uniform heat flux. The thermo-hydraulic effects of shapes and positions of obstacles mounted on upper wall referred to the bottom ribbed and grooved wall of the channel as well as its thermal enhancement factorare tested in a Reynolds number range of 3000 to 5000 with engine oil as working fluid. The numerical results demonstrate that combination of trapezoidal obstacles arrays of the upper wall placed against of ribs array of the bottom wall reveals highest thermal enhancement factor due to trapezoidal obstacles with increasing height in flow direction not only lead the flow to the bottom grooved wall but also the flow osculate surface of the obstacle and restart the thermal boundary layer with lowest friction factor compared to other cases.